Nanophotonic method for polycyclic aromatic hydrocarbons detection in water - Sushko, O. A.; Bilash, О. М.; Rozhitskii, M. M. (ISE, 2012)
Polycyclic aromatic hydrocarbons (PAHs) are the widespread environmental contaminants that can be found in atmosphere, water, soil, sediment and organisms. Among most dangerous PAHs is benzo[a]pyrene (BP). The effects of BP on health are: short-term when people are exposed to it at levels above the maximum contaminant level (MCL) (0.2 ppm) for relatively short periods of time leading to red blood cells damage, anemia ect; suppression of immune system and long-term, when human beings are exposured do BP influence at levels above the MCL namely effects on reproducibility and high probability of cancer illnesses. There are known methods for PAHs detection, such as chromatography, immuno-chemistry, biological and chemical ones. However, they have several disadvantages, including high cost, duration and complexity of the analysis procedure, the high detection limit and low selectivity. So at present a development of a new method of PAHs detection based on modern technologies and materials such as nanotechologies and nanomaterials. Belonging to above mentioned is nanophotonic method of PAHs assay. Nanophotonic method for PAHs detection in particular BP in water is a combination of electrochemical and electrochemiluminescence analysis with the application of nanomaterials and nanotechnologies. This method can be carried out using nanophotonic sensor based on nanomaterials such as semiconductor quantum dots (QDs).
Keywords: nanophotonic method; analyte; benzo[a]pyrene; electrochemiluminescence analysis